Wingate anaerobic test reference values for male power athletes - Coppin, E.; Heath, E. M.; Bressel, E.; Wagner, D. R. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The aim of this study was to develop reference values for the Wingate Anaerobic Test (WAnT) for peak power (PP), mean power (MP), and fatigue index (FI) in NCAA Division IA male athletes. Methods: Seventy-seven athletes (age 20.8 ± 1.8 y, mass 84.4 ± 9.4 kg, height 183.9 ± 6.2 cm) participating in American football (n = 52) and track and field (n = 25) performed a 30-s WAnT resisted at 0.085 kp/kg body mass (BM). Results: Absolute mean (± SD) values for PP and MP were 1084.2 ± 137.0 and 777.1 ± 80.9 W, respectively, whereas values normalized to BM were 12.9 ± 1.5 and 9.3 ± 0.9 W/kg BM, respectively. Mean FI values were 49.1% ± 8.4%. PP outputs >13.6, 12.4-13.6, and <12.4 W/kg BM were classified as high, medium, and low, respectively. MP outputs >9.8, 9.0-9.8, and <9.0 W/kg BM were classified as high, medium, and low, respectively. Conclusions: The reference values developed in this study can be used in various athletic training and research programs to more accurately assess athletes` anaerobic fitness and to monitor changes resulting from anaerobic training.